2017
DOI: 10.1161/jaha.117.002218
|View full text |Cite|
|
Sign up to set email alerts
|

Meditation and Cardiovascular Risk Reduction

Abstract: Despite numerous advances in the prevention and treatment of atherosclerosis, cardiovascular disease remains a leading cause of morbidity and mortality. Novel and inexpensive interventions that can contribute to the primary and secondary prevention of cardiovascular disease are of interest. Numerous studies have reported on the benefits of meditation. Meditation instruction and practice is widely accessible and inexpensive and may thus be a potential attractive cost‐effective adjunct to more traditional medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(85 citation statements)
references
References 125 publications
4
77
0
4
Order By: Relevance
“…84 Because certain psychosocial stressors (e.g., exposure to violence, low social position, and trauma) are disproportionately experienced by poor and minority communities in the United States, 85 investigating the underlying mechanisms through which such stressors operate to increase the risk of disease adds a critical piece of the puzzle in eliminating disparities in the burden of illness. 92,93 Religion and spirituality have emerged as potentially important sources of resiliency for minority and low-income communities, 94 and may be particularly important for African American and Hispanic/Latino communities who report higher levels of religious and spiritual beliefs and practices than White and Asian American populations. Human experiments show that both emotional and physical stressors trigger the central stress response and neuroendocrine systems, which can result in a cascade of hormonal changes linked to increased risk of obesity, metabolic syndrome, and poor glycemic control.…”
Section: Success Stories and Promising Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…84 Because certain psychosocial stressors (e.g., exposure to violence, low social position, and trauma) are disproportionately experienced by poor and minority communities in the United States, 85 investigating the underlying mechanisms through which such stressors operate to increase the risk of disease adds a critical piece of the puzzle in eliminating disparities in the burden of illness. 92,93 Religion and spirituality have emerged as potentially important sources of resiliency for minority and low-income communities, 94 and may be particularly important for African American and Hispanic/Latino communities who report higher levels of religious and spiritual beliefs and practices than White and Asian American populations. Human experiments show that both emotional and physical stressors trigger the central stress response and neuroendocrine systems, which can result in a cascade of hormonal changes linked to increased risk of obesity, metabolic syndrome, and poor glycemic control.…”
Section: Success Stories and Promising Approachesmentioning
confidence: 99%
“…Mind-body stress-reduction interventions, such as the Relaxation Response Resiliency (3RP) Program or meditation, for example, have been shown to enhance the expression of genes associated with favorable energy metabolism, insulin secretion, and telomere maintenance; 90,91 and suggest a positive benefit for cardiovascular health and reducing blood glucose levels. 92,93 Religion and spirituality have emerged as potentially important sources of resiliency for minority and low-income communities, 94 and may be particularly important for African American and Hispanic/Latino communities who report higher levels of religious and spiritual beliefs and practices than White and Asian American populations. 95 In a recent national study of African American women in the United States; for example, those who used religion or spirituality to cope with stress were significantly less likely to develop hypertension, and this protective effect was greater among those with the highest levels of perceived stress.…”
Section: Success Stories and Promising Approachesmentioning
confidence: 99%
“…A broad variety of hypothetical and potential effects of meditation on neurophysiology and neuroanatomy have been published so far. 7,8 Anatomical and structural changes, such as tissue augmentation of the cerebral cortex, subcortical grey and white matter, as well as the cerebellum and brain stem, were discussed, and an increasing number of studies suggest that different meditation practices show distinct patterns of brain activity. 1,7,9,10 Moreover, improvement in the subjectively experienced levels of general stress, depression and quality of sleep have been reported.…”
Section: Neurology and Psychologymentioning
confidence: 99%
“…1,7,9,10 Moreover, improvement in the subjectively experienced levels of general stress, depression and quality of sleep have been reported. 8,[11][12][13][14][15][16][17][18][19][20][21][22] Additionally, alterations on a neurophysiological level have been suggested.…”
Section: Neurology and Psychologymentioning
confidence: 99%
“…7 A recent American Heart Association (AHA) Scientific Statement on Meditation and Cardiovascular Risk Reduction suggested that stress reduction with meditation may be useful in the prevention of cardiovascular disease. 8 The Transcenden-Stress Reduction for Preventing LVH -Schneider et al tal Meditation technique has been found to be distinctly effective in primary and secondary prevention of CVD morbidity and mortality in African Americans and Whites. 9,10 A recent scientific statement from the American Heart Association emphasized "the potential for interventions that promote positive psychological health and reduce stress levels (for) improving health behaviors and ultimately health outcomes of African Americans."…”
Section: Introductionmentioning
confidence: 99%